Francesca Giovagnorio. Dediche votive private attiche del IV sec. a. C. Il culto di Atena e delle divinità mediche. - Palermo, Rocco (Journal of Greek Archaeology, 2018)
In this relatively short essay, the author discusses the historical and religious background of the 4th c. BC Attic dedicatory offerings, their archaeological and artistic contexts, and their inscriptions. In particular she addresses the cult of Athena according to the epithets attested for the Goddess in that period (= Athena Ergane, i.e.) and the health deities, among whom are Asklepios and Amynos.